A utopia da ordem: o ressentimento castrense em relação às acusações sobre o exercício do poder durante o movimento civil-militar no Brasil (1964-1974) - Santos, Thiago Dias (2011)
The respective work has as prism to analyze a series of testimonies given by military officers who participated in the political events in Brazil that culminated on the 31st of March of 1964. The deponents had a relevant role during the 21 years of the military government. The goal of the analysis concentrates on notes that exhibit throughout the testimonies, the resentments that the men in uniform exposed in their words. Resentments intensified mostly in the anticommunism and in the bad reputation the military forces had before the society after the end of the regime. The work is structured in showing how it began in the Brazilian army the role of an institution that was supposed to practice a direct political participation in the country, besides seeing itself like the source of moral reserve of the nation and guardian of the precepts of patriotism and nationalism. Being this done to demonstrate that the intervention which occurred in 1964 was not a result of an immediacy or by foreign orders in collusion with the national capital, where the soldiers would be mere playthings. The intervention needs to be analyzed from an optics that realizes the motives and intentions that made the military forces deprive the president John Goulart from the power. Among the testimonies it will also be analyzed the question of the military officers’ memory regarding subjects directly connected to the period: the reason of the destitution of João Goulart, the repression to the opponents, the question of torture and other recurrent subjects to the analyzed period. Among the testimonies it will also be analyzed the question of the memory of the military officers regarding subjects directly connected to the period: the reason of deposing João Goulart, the repression to the opponents, the question of torture and other recurrent subjects to the analyzed period. The conclusion of the work will be originated from a direct analysis of the testimonies where it is exposed in an explicit or implicit way, the resentments of the military officers regarding the occurrences before and after the events of the 31st of March of 1964.